PEMANFAATAN TUMBUHAN OBAT OLEH MASYARAKAT DI SEKITAR AREAL IUPHHK-HTIPT.BHATARA ALAM LESTARI DI KABUPATEN MEMPAWAH - I'ismi, Benedikta; Herawatiningsih, Ratna; Muflihati, . (Universitas Tanjungpura, 2018)
Medicinal plants are plants that on certain parts of the roots, stems, skin, leaves and excretion is believed by the community to cure or reduce pain. The are of IUPHHK-HTI PT.BAL is a region in which there are still many medicinal plants that are utilized by the community in tradisonal medicine. This study aims to determine the utilization of tradisonal medicinal plants in the are of IUPHHK-HTI PT.BAL used by the community of Sadaniang village.The method used in the filed is explorative. Data collection on the community was done by interviewing the respondents selected by snowball sampling and field obsrvation. The results of the study found 28 spesies of medicinal plants consisting of 24 familes, where Asterceae and Orchidaceae is the most plant families encountered. Habitus of medicinal plants is mostly tree. The most widely used plant part is the leaf part. The way of processing medicinal plants by boiling, crushed, dried, and without processed. How the use of medicinal plants is mostly in the form of a single material that can be consumed directly or indirectly. How to use medicinal plants for the most dominant healing that is by drunk and others eaten, pasted, gargle and shipped the wound.Keywords:, Asterceae, Medicinal Plants, Orchidaceae